(N|KSPERIMENTALXNYE METODY ISSLEDOWANIQ ASTROFIZI^ESKIH I GEOFIZI^ESKIH QWLENIJ (B:s ((NsBORNIK NAU^NYH TRUDOW(B) /s ((NlENINGRAD (B:s (Nfti(B,s, 1988)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(NrEZ(B. (NST(B.: (NANGL(B.s
(Nan sssr(B, (NfIZ(B.-(NTEHN(B. (NIN(B-(NT IM(B. (Na(B.(Nf(B. (NiOFFEs
Keywords: (NaSTRONOMI^ESKIE NABL@DENIQs; (NgEOFIZI^ESKIE ISSLEDOWANIQ s